Effectiveness of orange almond potato cookie vs. orange potato cookie supplementation on nutritional wellbeing of the Indonesian stunted preschool-aged children during COVID-19 pandemic - Fatmah, Fatmah; Utomo, Suyud W. (Frontiers in Nutrition, 2023)
Background Preschool-aged children who experience stunting due to insufficient consumption of macro- and micronutrients exhibit weakened immune systems, rendering them susceptible to contracting COVID-19 during the ongoing epidemic. Therefore, it is imperative to implement interventions aimed at enhancing the nutritional status of preschool-aged children by providing them with nutrient-rich food supplements as a preventive measure against illness transmission. The objective of the study was to evaluate the impact of incorporating potato almond orange cookies into the diet on the nutritional status of preschool-aged children who are experiencing stunting. Methods A non-randomized pre-post intervention study was done on 42 individuals aged 12–58 months during 4 weeks. The intervention group was provided with almond potato cookies, while the control group was given orange potato cookies. During the study period, educational sessions on balanced nutrition in preschool-aged children with stunting and COVID-19 were provided to the mothers of both groups. The data analysis involved conducting univariate and bivariate analyses, namely utilizing the independent t-test. Results The intervention group exhibited the most significant enhancements in -for-Age Z-score. The mean -for-Age Z-score of the intervention group increased by 0.51 (from −3.15 to −2.64), whereas the control group saw a smaller gain of 0.25 (from −2.69 to −2.44). This increase was influenced by the mother’s age; mother’s education; father’s occupation; family size; good sanitation facilities; healthy home environment; and fat, calcium, and zinc intake from the cookies (p < 0.05). From the perspective of knowledge about balanced nutrition and COVID-19, there was no significant difference in the -for-Age Z-score in the intervention group. Conclusion The ingestion of orange almond potato cookies has the potential to enhance the nutritional wellbeing of children in the preschool age group who are experiencing stunted growth.